Internationalization Towards Fostering School Culture of Quality: Practices and Perceived Impact - Robiños, John Robby O.; Alcazaren, Holden Kenneth G. (Philippine Journal of Education Studies (formerly the Education Quarterly), 2024)
Across the globe, internationalization has influenced the emphasis of educational institutions on international engagement and standardization aligned with global competencies. As Philippine higher education also aimed for internationalization, many universities were tasked to enhance their quality assurance framework by ensuring sound graduate mobility and strong international linkages. With these changes in education, this current study tried to identify existing internationalization practices and their perceived impact in three selected autonomous universities in the country. This study determined how these practices generated an educational paradigm shift toward a culture of quality through internationalization. Employing a qualitative-descriptive approach, structured online interviews were conducted with selected participants (n=14) closely associated with internationalization policies and initiatives in their respective universities. Based on a thematic analysis, the participants identified strategies involving incentivizing and strengthening of international linkages as effective practices for internationalization. Additionally, participants explained how these practices not only enhanced their skills but also enabled them to have international recognition. The findings provided grounding and insights on how to achieve a culture of quality through internationalization.